POLITICS OF CONTEMPORARY “SILK ROADS” - A. I. Litvinov (MGIMO University Press, 2016)
Recently in mass media we can find the idea about a new Silk Road or the concept of "Silk Road Economic Belt" which has been formulated by the Chinese PresidentXi Jinping on September 7,2013, during his official visit to Kazakhstan. This project is not only the creation of a transport, power and trade corridor, and also the project which will promote development of tourism in the region and to strengthening of cultural exchanges of China with the countries of Central Asia, it also includes construction of a network of high-speed fiber-optical networks. The economic strip of the Silk Road will begin in China and pass across the Central and the Southern Asia, part of branches across the territory of the Russian Federation and to leave to Europe. This international investment project assumes creation of a continental transport way. For implementation of overland part of "A great Silk Road is a three railway corridors (northern, central have to be constructed and southern) They have form a basis for development of other means of transport, including automobile subsequently. Construction of these three railway corridors acts as the most important and necessary stage of implementation of the project. The government of China declares that creation of an economic belt of the Silk way is a revival of once prospering trade-transport and cultural corridor from Asia to Europe which will promote activization of a friendly exchange between the people of the different countries. Further all this has to connect trade and economic space of Europe and Asia in a whole that has to serve implementation of deeper economic cooperation, between the countries participating in him, to increase in a trade turnover and expansion of scientific and technical exchanges between them.